PEMBELAJARAN BERBASIS TRI HITA KARANA MELALUI METODE BERCERITA DALAM MENGOPTIMALKAN PERKEMBANGAN NILAI AGAMA DAN MORAL ANAK KELOMPOK B-B1 PADA TK. BHAKTI YOGA KUMARA DESA KUWUM KECAMATAN MENGWI KABUPATEN BADUNG - Dian Wahyu Lestari; Aria Prima Dewi PF Kadek; Nanduq Ferninandus (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2021)
Early childhood is an individual who is in a golden age, where 80% of human development occurs at an early age. Providing good stimulation is an obligation for early childhood educators so that children's development can develop properly. Early childhood education cannot be separated from storytelling because through the method of telling children, children can develop their imagination into new knowledge. The development of religious and moral values in early childhood is a very hot problem in this era of globalization because of the decline in moral values that exist in our country. Through these problems, it is very necessary to create learning that can develop religious and moral values from an early age. One of the Hindu religious lessons that can be given to children is Tri Hita Karana. By combining learning in early childhood education, namely the storytelling method with the introduction of the concept of Hinduism, namely Tri Hita Karana, it is hoped that it can develop moral and religious abilities in early childhood. Right-kindergarten is a form of early childhood education on the formal track that organizes educational programs for children aged 4 to 6 years. The age of 4-6 years is an important sensitive period for children to get an education. The experiences children get from the environment, including stimulation provided by adults, will affect their lives in the future. Tri Hita Karana-based learning applied in Kindergarten aims to provide early learning for children so that they have a simple basic understanding of tri hita karana. The formulation of the problem of this research is: Whether Tri Hita Karana Based Learning Through Storytelling Method can optimize the Religious and Moral values of Group B-B1 children in kindergarten. Bhakti Yoga Kumara Kuwum, Mengwi District, Badung Regency ?. The theory used in this research is the moral theory. This type of research is a type of classroom action research where the researcher is directly involved in the class and observes the facts. Data collection methods used are test methods, interview methods and observation methods